Practical work in science education: a systematic literature review - Oliveira, Hugo; Bonito, Jorge (Frontiers in Education, 2023)
Practical work has taken a leading role in science teaching, particularly since the 1960s. Its goals are mainly oriented toward the development of sensitivity and taste for the study of physical and natural phenomena, bringing students closer to the daily reality experienced by researchers working in these areas of knowledge, while promoting educational success. However, these purposes have not always been achieved so, over time, limitations to the way that practical work has been developed have also been identified. In order to recognize the current state of the art on the development of the practical work in the teaching of sciences, a systematic literature review was designed, especially focused on the definition of the concept of practical work, its advantages, evaluation methodologies, and the criticism/limitations attributed to its implementation. To this end, four databases and one aggregator were used, to identify 53 international scientific publications. Analysis of this corpus allowed the identification of 8 categories associated to the concept of practical work, 5 categories associated to its advantages, 6 categories with the types/methodologies of evaluation and 5 categories associated with the limitations of this methodology. (From this analysis) it is concluded that most authors considers that the main idea integrative idea of the concept of practical work should be the manipulation of materials in practical activities (hands-on style), and the main advantage of this methodology comes from the fusion between the development of practical skills and the conceptual understanding (minds-on). In the evaluation methods, the context, procedures and specific instruments are favored and the main limitation pointed to this methodology is that the way practical work is implemented, is often not in agreement with the methods and techniques used by scientists and researchers.